2017
DOI: 10.1186/s12885-017-3295-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rebamipide liquid for chemoradiotherapy-induced oral mucositis in patients with head and neck cancer: a multicenter, randomized, double-blind, placebo-controlled, parallel-group phase II study

Abstract: BackgroundRecent preclinical and phase I studies have reported that rebamipide decreased the severity of chemoradiotherapy-induced oral mucositis in patients with oral cancer. This placebo-controlled randomized phase II study assessed the clinical benefit of rebamipide in reducing the incidence of severe chemoradiotherapy-induced oral mucositis in patients with head and neck cancer (HNC).MethodsPatients aged 20–75 years with HNC who were scheduled to receive chemoradiotherapy were enrolled. Patients were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Taxanes, platinum-containing drugs, and FUs are all reported to cause mucosal damage, with an incidence of up to 70% [ 11 , 12 ]. However, several countermeasures to prevent OM with chemo(radio)therapy have been reported [ 13 15 ], those effects might not be sufficient for multidrug anticancer agents. A report indicated that the oral glutamine (Gln) administration reduced the duration and severity of OM after cytotoxic cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Taxanes, platinum-containing drugs, and FUs are all reported to cause mucosal damage, with an incidence of up to 70% [ 11 , 12 ]. However, several countermeasures to prevent OM with chemo(radio)therapy have been reported [ 13 15 ], those effects might not be sufficient for multidrug anticancer agents. A report indicated that the oral glutamine (Gln) administration reduced the duration and severity of OM after cytotoxic cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the original trial (a multicenter, randomized, double-blind, placebo-controlled, dose-ranging, phase 2 trial; ClinicalTrials.gov identifier: NCT02085460) has been already published in detail [ 13 ]. Briefly, patients with histopathological diagnosis of primary tumor scheduled to undergo definitive or postoperative CRT to head and/or neck were eligible for enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…We employed the incidence of severe OM in clinical examination determined by INV to compare with the incidence of severe OM in clinical examination determined by ICR, and determined the difference in evaluations scored between ICR and INV, the primary end point of the current post hoc study. The difference in the incidences of severe OM (grade ≥ 3) between the respective groups was evaluated through Chi square test [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cryotherapy prevented stomatitis in patients receiving bolus doses of 5-fluorouracil and haematopoietic stem cell transplantation 5. Rebamipide is an internal-use mucosal protectant, and gargling with rebamipide has been reported to prevent stomatitis in patients with head and neck cancer who are receiving chemoradiotherapy 6 7. However, recommendations for preventing chemotherapy-induced stomatitis in patients with breast cancer are lacking.…”
Section: Introductionmentioning
confidence: 99%